Pemahaman Desain Produk dengan Pendekatan Sejarah Desain dan Peran Desain - Malik, Kendall; Fernando, Ferry; Gani, Maulid Hariri; Fajrina, Rahma Melisha; Utami, Mira (INSTITUT SENI INDONESIA PADANGPANJANG, 2023)
History says that design is actually rooted in artistic activities that have grown towards one sphere of culture in its essence to another: the means of everyday human life. When historical descriptions state that the primitive people make cangulals as a tool that is a transformation of the extension of the hand: often questions about design, art or technology. Design is challenged to have to engage in a variety of cultural weather. As with technology, design is required to immediately formulate the situation in line with the development of other cultural sectors. The construction of the Bauhus in Germany, with the prophecy of Walter Gropius, is considered a milestone in the development of modern design history. The basic philosophy of the Bauhaus departs from the idea that the methods of industrial production of the 19th century have led to the disregard of the relationship between the process of design and handicraft or the ability of the hand, the unity between the creator and the product is broken. In fact, the influence, the Bauhaus principles that later evolved into an International style, were not the product of experiments produced by the instructors (Meister) and his students, but the methodology of visual arts education and the design methodology that he taught. The fundamental role of a designer will never change, but what will change is his commercial situation. Technology, research, and manufacturing techniques of different products drive manufacturers to produce similar items. Keywords: History; Product Design; Design Role